(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: Describe the current status of knowledge and attitudes of primary caregivers in managing and caring for schizophrenic patients at Thanh Hoa Provincial Mental Hospital in 2025. Methods: Cross-sectional descriptive study with non-probability convenience sampling method, pre-designed instrument set. Results: 100% of caregivers know that they need to receive monthly medication for their patients, but only 75% know how to give medication to their patients. 89.3% of caregivers have the correct knowledge to handle side effects of medication. 93.8% of caregivers have correct knowledge of nutritional care for patients, 62.5% have correct knowledge in supporting patients in labor, and 97.3% handle correctly when patients show worsening symptoms. Conclusion: Knowledge, attitude towards management and care of schizophrenic patients of primary caregivers were relatively good with 64.3% having good knowledge and 66.1% having positive attitude.